SIMULATION OF ADAPTIVE BEHAVIOR IN THE CONTEXT OF SOLVING AN AUTONOMOUS ROBOTIC VEHICLE MOTION TASK ON TWO-DIMENSIONAL PLANE WITH OBSTACLES - R. A. Prakapovich (Informatika)
An adaptive neurocontroller for autonomous robotic vehicle control, which is designed to generate control signals (according to preprogrammed motion algorithm) and to develop individual reactions to some external impacts during functioning process, that allows the robot to adapt to external environment changes, is suggested. To debug and test the proposed neurocontroller a specially designed program, able to simulate the sensory and executive systems operation of the robotic vehicle, is used.